Crystal structure of catena-poly[(μ3-2-carboxy-4-(3-carboxy-5-carboxylatophenoxy)benzoato-κ3O:O′:O′′)-bis(μ2-4,4′-bis(pyrid-4-yl)biphenyl-k1N)copper(II)], C60H40N4O9Cu - Li Shi-Hui; Tang Qian-Qian (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C60H40N4O9Cu, triclinic, P1̄ (no. 2), a = 9.6569(8) Å, b = 10.3941(7) Å, c = 24.9421(16) Å, α = 97.162(5)°, β = 90.953(6)°, γ = 107.788(7)°, V = 2361.3(3) Å3, Z = 2, Rgt(F) = 0.0729, wRref(F2) = 0.1609, T = 293(2) K.